Laporan Pertama Infeksi Begomovirus pada Tanaman Mentimun di Bali - I Dewa Made Putra Wiratama; Gusti Ngurah Alit Susanta Wirya; I Dewa Nyoman Nyana; Ni Nengah Putri Adnyani; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Leaf yellowing symptoms was commonly found in cucumber plants in Bali provinces, i.e. in Apuan and Bangli villages recently. Begomovirus infection is suspected as the causal agent, due to similar symptoms previously reported from cucumber plants in Java. In addition, Bemisia tabaci was observed in the field. The objective of this research was to identify the causal agent of leaf yellowing disease of cucumber in Bali. Virus detection and identification was conducted by polymerase chain reaction method using universal primers for Begomovirus, i.e. SPG1/SPG2. DNA fragment of 912 bp in size was successfully amplified from leaf samples. Analysis of nucleotide sequencing indicated that Begomovirus infecting cucumber plants in Bali has the highest homology (91%) with Squash leaf curl China virus (SLCCNV) isolate from Malaysia. This is the first report of SLCCNV infection in Bali.